Differentiated Learning Strategy in Dance Extracurricular Activities at SMA Negeri 2 Lumajang - Melly wulandari; Joko Winarko (Jurnal Pendidikan Sendratasik, 2026)
The diversity of student characteristics in dance extracurricular activities, both in terms of abilities, interests, and learning styles, requires adaptive learning strategies so that each student can develop according to their potential. This study aims to describe the implementation of a differentiated learning strategy in dance extracurricular activities at SMA Negeri 2 Lumajang, identify supporting and inhibiting factors, and analyze student learning outcomes through its implementation. This study employed a qualitative approach with a descriptive approach. The research location was SMA Negeri 2 Lumajang, with subjects consisting of dance extracurricular instructors and students actively participating in the activities. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was achieved through triangulation of sources and techniques. The results showed that instructors implemented a differentiated learning strategy through differentiation of content, process, product, and learning environment tailored to students' abilities, interests, and characteristics. Supporting factors for the implementation of this strategy included school support, student motivation, instructor creativity, and collaboration among students. Inhibiting factors included differences in student abilities, limited facilities, limited practice time, and psychological challenges. The implementation of a differentiated learning strategy had a positive impact on improving students' dance skills, creativity, self-confidence, collaboration, and responsibility. Thus, differentiated learning is an effective and relevant approach to accommodate student diversity in dance extracurricular activities and support the implementation of the Independent Curriculum.